Correlation approach for the Push-Out and full-size bending short-term performances of timber-to-timber slabs with Self-Tapping Screws. (1st July 2021) - Bedon, Chiara; Sciomenta, Martina; Fragiacomo, Massimo
Highlights: Push-Out and full-size bending experimental tests are investigated. Special care is spent for timber-to-timber slabs with Self-Tapping Screws (STSs). The mechanical properties of STS joints are derived from full 3D models. Numerical results are validated towards experiments and analytical models of literature. A correlation is found to capture the mechanical properties from Push-Out to bending setup. Abstract: Self-Tapping Screws (STSs) are commonly used to realize many geometrical configurations for connections that are characterized by enhanced stiffness and load-carrying capacity. The analysis of STS joints and composite systems, however, usually requires designers to account for several aspects in their actual load transfer mechanisms, and most of them require refined calculation tools. In this paper, an extended Finite Element (FE) investigation is proposed for timber-to-timber slabs with STS joints, based on full 3D brick models inclusive of Cohesive Zone Modelling (CZM) techniques and damage constitutive laws for the materials in use. The final goal of the study takes advantage of the global and local performance assessment of a selection of STS joints, with careful consideration for their response under a conventional Push-Out (PO) test setup or a full-size bending configuration. As shown, major FE outcomes are discussed to elaborate a design procedure that can be developed on the base of correlation coefficients for maximum force and stiffness calculations in a given slab and loading condition. Major effects due to variable loading configurations are in fact explored at the screw level. Further, geometrically simplified spring-based FE models, that hardly capture the complex behaviour of the examined systems but are largely used in design practice, are presented in comparison to refined FE approaches and literature efforts. As shown, the variation of maximum force and stiffness parameters for STSs is emphasized in the paper for a selection of configurations, and fitting curves are proposed to estimate the STS performance along a given full-size slab, thus suggesting the feasibility and possible generalization of the procedure.